2020
DOI: 10.4274/tjod.galenos.2020.05695
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy associated plasma protein A: An indicator of adverse obstetric outcomes in a South India population

Abstract: İlk trimester anöploidi taraması (FTAS), Hindistan'daki merkezlerin çoğunda doğum öncesi bakımın ayrılmaz bir parçası haline gelmiştir. FTAS için kullanılan serum belirteçleri hamilelikle ilişkili plazma protein A (PAPP-A) ve beta insan koryonik gonadotropindir. Bu çalışmada spesifik olumsuz fetal maternal olaylarda PAPP-A'nın rolünü değerlendirmeyi amaçladık. Güney Hindistan'da FTAS tarama testinde düşük maternal PAPP-A (≤5 persentil) ile gebelik sonuçlarını analiz etmek ve bunları >5 persentil değerine sahip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Emerging evidence suggests that low PAPP-A levels are associated with fetal rejection, compromised placentation, and a range of complications including spontaneous abortion, preterm delivery, fetal growth restriction, preeclampsia, and stillbirth. The influential FASTER trial found that PAPP-A levels below the 5th percentile were linked to an increased risk of fetal growth restriction, spontaneous abortions, preterm delivery, low birth weight, preeclampsia, and placental abruption, and these results were consistent with findings from other studies (6,8).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Emerging evidence suggests that low PAPP-A levels are associated with fetal rejection, compromised placentation, and a range of complications including spontaneous abortion, preterm delivery, fetal growth restriction, preeclampsia, and stillbirth. The influential FASTER trial found that PAPP-A levels below the 5th percentile were linked to an increased risk of fetal growth restriction, spontaneous abortions, preterm delivery, low birth weight, preeclampsia, and placental abruption, and these results were consistent with findings from other studies (6,8).…”
Section: Introductionsupporting
confidence: 85%
“…Additionally, IGF regulates the uptake of glucose and amino acids, thereby influencing fetal growth. Thus, PAPP-A is involved in the regulation of IGF activity (5)(6)(7). Emerging evidence suggests that low PAPP-A levels are associated with fetal rejection, compromised placentation, and a range of complications including spontaneous abortion, preterm delivery, fetal growth restriction, preeclampsia, and stillbirth.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our results, the highest association of low level PAPP-A was seen with IUGR. In this context, other reports have shown IUGR to be more associated with low maternal serum PAPP-A ( 20 , 21 ). Only in one research no association between low level PAPP-A and IUGR is reported ( 22 ).…”
Section: Discussionmentioning
confidence: 76%
“…It appears in circulation after blastocyst implantation. A low serum concentration of PAPP-A after 24 weeks of pregnancy is significantly correlated with placental dysfunction, stillbirth, PTB, intrauterine or fetal growth restriction, and fetal death [71]. The neuropeptide urocortin, produced by amnion and chorion, encourages prostaglandin-mediated delivery through uterine contraction.…”
Section: Proteomic Biomarkersmentioning
confidence: 99%